ANALISIS TINGKAT KEPUASAN PASIEN ANALISIS TINGKAT KEPUASAN PASIEN RAWAT JALAN PESERTA BPJS KESEHATAN TERHADAP PELAYANAN FARMASI DI INSTALASI RSU SEMBIRING - Anggun Syafitri; Bintang Lubis; Jhan Saberlan Purba; Sri Sudewi Pratiwi Sitio; Efrata Sembiring; Yunita Syaputri Damanik (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Quality health services are health services that can satisfy every user of health services in accordance with the level of satisfaction. Satisfaction will occur if the expectations of the patient can be met by the services provided by the hospital so that it needs to be considered continuously the satisfaction and expectations of the patient. The purpose of this study was to determine the level of satisfaction of outpatients of BPJS Kesehatan participants with pharmaceutical services at the outpatient Pharmacy Installation at RSU Sembiring. The design of this study used descriptive survey research. The population in this study was 1400 patients, and the sample was 93 patients using the Slovin formula. Data collected through primary and secondary data and using univariant and bivariant analysis with the help of the SPSS computer program. The results of the chi square test obtained variables related to the satisfaction of outpatients at the general hospital, namely: Physical evidence (p value = 0.002), Reliability (p value = 0.000, Responsiveness (p value = 0.002), Guarantee (p value = 0.004), and Empathy (p value = 0.000). It is recommended to the Outpatient Pharmacy of Sembiring General Hospital to maintain a good quality of service and continue to improve the quality of service to patients.